ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH DI KOTA BINJAI - Dhea Rizki Aulia; Murtala Murtala; Mutia Rahmah (Jurnal Ekonomi Regional Unimal, 2022)
The purpose of this study was to determine the analysis of the factors that affect local revenue. This study aims to analyze and find out how much influence the variables of government expenditure, population, GRDP and local taxes have on local revenue in Binjai City. The data sources were obtained from the Central Statistics Agency (BPS) of Binjai City, the Regional Revenue and Asset Financial Management Agency (BPKPAD), supporting books, journals and other articles. The analytical method used in this study is multiple linier regression using the dependent variable, namely local revenue (PAD) while the independent variables are government spending, population, GRDP, and local taxes rom 2012 to 2021. Based on the results of the analysis, it can be concluded that concluded : 1) Partially the variable Government Expenditure (X1) has a significant effect on PAD (Y) in the city of Binjai, 2) Partially the variable Total Population (X2) has asignificant effect on PAD (Y) in the city of Binjai, 3) Partially the variable GRDP (X3) has no significant effect on PAD (Y) in the city Binjai, 4) Partially the Regional Tax variable (X4) has a significant effect on PAD (Y) in the city of Binjai.